Assessment of metabolic profile and ischemia-modified albumin level in patients with alopecia areata: A case-control study - Pinar Incel-Uysal; Neslihan Akdogan; Nuran Alli; Ayse Oktem; Tuba Candar; Canan Topcuoglu; Turan Turhan (Wolters Kluwer Medknow Publications, 2019)
Background: Alopecia areata (AA) is an autoimmune-mediated hair follicle disorder. In the literature, there is no study evaluating metabolic syndrome and levels of ischemia-modified albumin (IMA) which is proposed as an oxidative stress biomarker in patients with AA. Aims: The aim was to investigate the presence of metabolic syndrome and the levels of IMA, small dense low-density lipoprotein (sd-LDL), and visfatin levels in AA patients. Settings and Design: A hospital-based cross-sectional study was undertaken among AA patients and controls. Subjects and Methods: Thirty-five patients with AA and 35 sex-, age-, and body mass index-matched healthy controls were enrolled. Clinical and laboratory parameters of metabolic syndrome were examined in all participants. Furthermore, IMA, sd-LDL, and visfatin levels were assessed and analyzed with regard to disease pattern, severity and extent, severity of alopecia tool score, duration, and recurrence. Results: The median IMA and adjusted IMA levels were significantly increased compared with controls (P < 0.05 and P =0.002, respectively). Patients with pull test positivity displayed higher levels of adjusted IMA levels (P < 0.05). In AA group, there was a positive correlation between adjusted IMA and waist circumference (r =0.443, P =0.008), adjusted IMA and triglyceride levels (r =0.535, P =0.001), and adjusted IMA and sd-LDL levels (r =0.46, P < 0.05). We observed no statistically significant difference in fasting blood glucose and lipid profile, sd-LDL, and visfatin levels of the patients and healthy controls. Conclusions: AA patients and controls have similar metabolic profile. Raised levels of adjusted IMA levels may be associated with antioxidant/oxidant imbalance and with risk of cardiovascular disease.